Limnology of Lake Ashura, Dinajpur, Bangladesh - Alfasane, Md Almujaddade; Gani, Md Ataul; Islam, Md Shafiqul; Khondker, Moniruzzaman (Bangladesh Journal of Botany, 2012)
Results of limnological investigation of lake Ashura showed that air and water temperatures were 31.5 ± 0.25ºC and 30.0 ± 0.45ºC, respectively in the month of April, 2011. pH, alkalinity, conductivity, dissolved oxygen and TDS of water were 7.11 ± 0.02, 2.96 ± 0.58 meq/l, 760.67 ± 8.08 ?S/cm, 7.72 ± 0.41 mg/l and 104.67 ± 1.53 mg/l, respectively. The concentration of NO3-N, SRP and SRS were 63.33 ± 25.16 ?g/l, 11.60 ± 1.60 ?g/l and 14.36 ± 0.25 mg/l, respectively. Phytoplankton biomass as chl a and concentration of phaeopigment were 5.33 and 3.41 ?g/l, respectively. The density of phytoplankton was 552.84 × 103 ind/l. A total of 35 species of phytoplankton were recorded of which 15 belonged to Euglenophyceae, followed by Chlorophyceae (8), Bacillariophyceae (7), Cyanophyceae (4) and Cryptophyceae (1). Macrophyte flora was represented by 31 species. The dominant species were Eichhornia crassipes (Mart.) Solms, Ludwigia adscendens (L.) Hara. and Oryza sativa L. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11081 Bangladesh J. Bot. 41(1): 43-48, 2012 (June)